Peningkatan Partisipasi Masyarakat melalui Penanaman Mangrove dalam Rehabilitasi Pesisir - Lasaiba, Mohammad Amin (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Mangrove plantation is one of the efforts to rehabilitate damaged coastal ecosystems. This research was conducted in Negeri Wakal, a village in the coastal region of Jazirah Leihitu, Central Maluku Regency. This activity aimed to rehabilitate the coastal ecosystem while increasing community participation. The method was through lectures and mangrove planting training involving the surrounding community as participants, accompanied by Geography Nature Lovers students and supervising lecturers. The results showed that the mangrove planting activity in Negeri Wakal was successfully carried out. The activity was also successful due to the good participation and enthusiasm of the community. The evaluation of this activity stated that the location still requires many mangrove seedlings to be rehabilitated and a system of community assistance is also needed to maintain the planted mangroves.